Study of pattern of adverse drug reaction due to cancer chemotherapy and their management in hospitalized patient in B P koirala Memorial Cancer Hospital - Thapaliya, K; Shrestha, A; Prajapti, A; Subedi, R; Giri, S (Journal of Chitwan Medical College, 2015)
Adverse Drug Reactions (ADRs) are a global problem adding to the economic burden of the society. Anti-cancer drugs are prone to cause ADRs and there is lack of pharmacovigillance data on such type drugs. Therefore, the present study was undertaken to monitor suspected ADRs in the cancer chemotherapy with its management in B.P. Koirala Memorial Cancer Hospital (BPKMCH). The study was done in the inpatient department of BPKMCH from May, 2014 to July, 2014, among the patients receiving chemotherapy. It was a hospital based prospective observational study. Most commonly occurring cancer were lung (16%), ovary (15%), cervix (11%), breast, blood, and throat (9%). Most frequently used drugs for cancer chemotherapy were paclitaxel (25%), cyclophosphamide (18%), vincristine (9%), cisplatin (11%) and adriamycin (6%). Most common ADRs experienced were nausea & vomiting (85.45%), loss of appetite (72.72%), mucositis (65.45%), pain (63.63%), loss of breath (40%), constipation (52.72%) and polyneuropathy (58.18%). DOI:http://dx.doi.org/10.3126/jcmc.v4i4.11967